'A new life in the countryside awaits'*: interactive lessons in the rural utopia in 'farming' simulation games. Issue 3 (4th May 2017) - Cole, Matthew; Stewart, Kate
ABSTRACT: This paper critically analyses the legitimation of exploitative human–nonhuman animal relations in online 'farming' simulation games, especially the game Hay Day. The analysis contributes to a wider project of critical analyses of popular culture representations of nonhuman animals. The paper argues that legitimation is effected in Hay Day and cognate games through: the construction of idyllic rural utopias in gameplay, imagery, and soundscape; the depiction of anthropomorphized nonhumans who are complicit in their own subjection; the suppression of references to suffering, death, and sexual reproduction among 'farmed' animals; and the colonialist transmission of Western norms of nonhuman animal use and food practices among the global audience of players. Hay Day thereby resonates with the wider cultural legitimation of nonhuman animal exploitation through establishing emotional connections with idealized representations of nonhuman animals at the same time as they inhibit the development of awareness and empathy about the exploitation of real nonhuman animals.